Estudo da capacidade de amplificação do sinal de fluorescência de anticorpos conjugados com nanopartículas de ouro detectado por citometria de fluxo. - Daniela Silva dos Reis (2019)
The use of nanomaterials in the biomedical area is gradually increasing with the improvement of synthesis and functionalization techniques. In order to be used safely, the nanomaterial must be highly stable and have low toxicity. In this work it was proposed to study the possibility of amplifying the fluorescence signal, using low concentrations of primary antibodies functionalized with gold nanoparticles (AuNP) and secondary ones also in low concentrations and to carry out a systematic study of their stability and low toxicity to cells. Pure AuNPs were chosen because they do not emit a fluorescence signal after being intercepted by a light source, for their high capacity for energy absorption and transfer and for not causing toxicity to known cells and for being highly stable. This work involved the following steps: a) synthesis of AuNPs by the sodium citrate route; b) characterization of AuNPs in terms of size and morphology; c) evaluation of cell viability and cell cycle; d) biofunctionalization of AuNPs with primary and secondary antibodies. For this, the primary antibodies cetuximab (CetIgG) and anti-CD44 (CD44IgG) were used, for the latter the identification of its isoelectric point by the solution pH variation curve and the secondary antibodies Alexa Fluor®488IgG were used (AF488IgG) and Pe-CF594 IgG1 (Pe-CF594IgG. E) characterization of the formed nanocomplexes; f) conjugation of nanocomplexes with secondary antibodies; g) evaluation of the binding of nanocomplexes to secondary antibodies; h) recognition of the target molecules present in the cell membrane by the nanocomplexes. The UV-vis spectra obtained showed the formation of gold nanoparticles, with a characteristic plasmonic band. After functionalization with CetIgG and CD44IgG, UV-vis spectroscopy was performed again, which demonstrated success in this procedure due to the displacement of the curves in relation to pure AuNPs. AuNPs were analyzed by electron microscopy (MET) that demonstrated their spherical morphology. The AuNPs stability study was carried out through measurements of dynamic light scattering (DLS). The zeta potential was performed to confirm the stability of the colloidal emulsion. AuNPs were evaluated before and after functionalization with primary antibodies the results showed that the nanoparticles remained dispersed. The fluorimetry test confirms the AuNPs functionalization with CetIgG and CD44IgG, the results corroborate the data obtained by the zeta potential. To confirm the conservation of cell epitope recognition and amplification by the AuNPCetIgG and AuNPCD44IgG nanocomplexes at MET and flow cytometry (CF) and flow cytometry with image (CFI) were used. The data obtained by these techniques demonstrated that, after the functionalization of the primary antibodies with AuNPs, there was no impairment for recognition and binding to cell membrane receptors. There was also an improvement in signal detection at low concentrations by the secondary antibodies Alexa Fluor 488 (AF488IgG) and Pe-CF594IgG, generating more efficient results with narrower emission spectra, reducing interference in other filters and reducing the costs of the cytometry technique. flow.